2021
DOI: 10.1088/1402-4896/abdf84
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the impact of nonmagnetic Sc substitution on the magnetic properties of La2NiMnO6 double perovskite

Abstract: The structural, electronic, and magnetic properties of a sol-gel prepared series of La2Ni1−x Sc x MnO6 compounds have been extensively studied using x-ray diffraction, x-ray absorption near edge structure, and dc magnetization techniques, respectively. The entire series was isostructural and exhibited the La2NiMnO6 double perovskite P21/n monoclinic structure. The nonmagnetic Sc3+ substitution led to the evolution of competing magnetic phases in La2Ni1−x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These advantages have enormously boosted them in an upsurge application in spintronic devices. [1][2][3][4][5][6][7][8][9][10][11][12] Among the multitudinous double-perovskites, La 2 NiMnO 6 (abbreviated as LNMO) double-perovskite has beguiled great interest due to its high Curie point near room temperature. 4,[13][14][15][16][17][18][19] Particularly, the magnetic properties of LNMO thin films can be flexibly regulated by means of varying deposition parameters or employing the appropriate substrate wafers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These advantages have enormously boosted them in an upsurge application in spintronic devices. [1][2][3][4][5][6][7][8][9][10][11][12] Among the multitudinous double-perovskites, La 2 NiMnO 6 (abbreviated as LNMO) double-perovskite has beguiled great interest due to its high Curie point near room temperature. 4,[13][14][15][16][17][18][19] Particularly, the magnetic properties of LNMO thin films can be flexibly regulated by means of varying deposition parameters or employing the appropriate substrate wafers.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks for the significant coupling effect between lattice, charge, spin and orbit of different ions at multiple B‐sites in double‐perovskite compounds, they exhibit more abundant compositional variation as well as physical property tunability than the traditional single‐perovskites. These advantages have enormously boosted them in an upsurge application in spintronic devices 1–12 . Among the multitudinous double‐perovskites, La 2 NiMnO 6 (abbreviated as LNMO) double‐perovskite has beguiled great interest due to its high Curie point near room temperature 4,13–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetism in this compound is governed by the superexchange mechanism between the half-filled e g orbitals of Ni 2+ and the adjoining empty e g orbitals of Mn 4+ cations [15,16]. The magnetic, electronic, and transport properties of the compound are extremely sensitive to the ordering of Ni 2+ and Mn 4+ cations at two B-sites and can be modified by doping at A [17,18] or B [19][20][21] sites. It has been shown that the crystallographic structures, Curie temperatures, and saturation magnetizations of double perovskites can be well-tuned by controlling the ratio of the two B-site cations [6,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%